”Bedekeh” (Akit Tribal Ritual on Rupat Island in the Bengkalis Regency of Riau Province in the Global Era) - ., Suroyo (Udayana Journal of Social Sciences and Humanities, 2018)
The Akit community have localized knowledge and accumulated wisdom that is brought to bear in addressing health problems. Bedekeh treatment is a tradition that stems from the teachings of the ancestors and it is implemented when the Akit community was in need of treatment services for diseases. This study outlines the empirical evidence concerning the problems associated with the globalization of culture. There is conflict between the values of local and global culture. The data in this study was collected through observational techniques, in-depth interviews, literature studies, and documentation. The batin and bomoh both play an integral role in the Akit tribal life cycle. The influence of globalization have influenced the use of the traditional rituals of the Akit. This has accelerated the loss of Akit oral traditions. The existence of the Akit tribal has recently been impacted by marginalization due to a number of internal and external factors. There are a number of factors affecting the growing marginalization of ritual treatment by bomoh of the Akit in tribe situated in the village of Hutan Panjang on Rupat Island. Firstly, is the effect of religious conversions by some members of the Akit. Secondly, there is the negative stigma that people from other communities associated with witchcraft. And thirdly, the development of science and technology in the treatment of health issues; including the influence of formal and informal education on Akit community and those they come into contact with. The existence of the bedekeh ritual in the Akit is viewed essential to public service in a scientific research as a form of defence of a group of local traditions and the preservation of the culture of the nation.